EXTENSION-INDUCED METAMORPHISM - Ivanov S.N.; Rusin A.I. (My University, 1987)
Extensional processes predominate in the system of island arcs and marginal seas as confirmed by complexes of parallel dikes in the corresponding paleostructures and by seismic and other data in present-day marginal seas and arcs. Extension-induced deformations also apparently play a significant role in the orogenic period of foldbelt development, as indicated by zones of so-called reflected tectonomagmatic activation and rifting immediately before the intrusion of 'orogenic' granitic plutons. The authors developed a model which assumes that fractures close up at depths of about 10 to 15 km but are preserved at greater depths, below the compaction zone, except that then they exist as result of lithostatic pressure. In the zone of lithostatic pressure on the fluid, the strength of the crust not only ceases to increase, but actually approaches zero (or, more precisely, very low values) at the slow (10 -14 to 10 -15 sec -1) geological deformation rates. This model is supported by the evidence that no foci of earthquakes occurring under the extensional conditions are found below certain depths.